Crimes of traffic of influences -and influence peddling - Muñoz Lorente, José (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The crimes of traffic of influences and influences peddling are a manifestation of offenses relating to corruption in the Spanish Penal Code. Besides having a operation for themselves, usually they are considered as crimes "refuge" when you can not prove the existence of some typical elements of other more traditional corruption crimes such as prevarication or bribery. Moreover, it is patently subject to improvement offenses by the legislator and by the Court, especially the Supreme Court, which has been characterized in recent times, making very restrictive interpretations of traffic of influences that contribute little to promote the fight against corruption.
Keywords: Traffic of influences; influences peddling; corruption; impunity; restrictive judicial interpretations